Implementasi Ice Breaking Edukatif sebagai Strategi Menciptakan Konsentrasi dan Semangat Belajar Siswa di Kelas V Sekolah Dasar - Atep ramdani Ramdani; Nada Nabilah; Syifa’u Aulia Rahma; Ai Santi Solihat; M. Rafli Alghifari (Yayasan Al-Afif, 2025)
This study aims to describe the implementation of educational ice breaking as a strategy to foster concentration and learning enthusiasm among fifth-grade students at MIS Sukawening. The research was motivated by the common phenomenon of student fatigue, lack of focus, and low participation during lessons, particularly after break sessions when energy levels tend to decrease. A qualitative descriptive approach was employed, involving one classroom teacher and 25 students as participants. Data were collected through participatory observation, semi-structured interviews, and documentation of classroom activities. The findings reveal that educational ice breaking activities, designed in the form of thematic quizzes, concept-based games, short riddles, and simple physical exercises, successfully created a more engaging, dynamic, and inclusive learning atmosphere. These activities not only restored students’ focus but also enhanced their motivation, social interaction, and active participation in the learning process. Teachers reported that classroom management became easier, as the learning environment turned more conducive and filled with positive energy. These results align with previous studies which emphasize that educational ice breaking plays a significant role in improving interaction quality, learning outcomes, and students’ social development. Therefore, educational ice breaking deserves to be considered an integral strategy in elementary school lesson planning to create enjoyable, meaningful, and sustainable learning experiences.